Social and Economic Sufism: The Development and Role of Sufism in the Digital and Modern Era - Siswoyo Aris Munandar (Program studi Keagamaan Islam, 2023)
The objective of this study is to challenge the conventional wisdom that Sufism solely focuses on the afterlife by shedding light on the participation of Sufis in both religious and secular affairs. The qualitative descriptive research method has been employed to aptly illustrate the typology of modern-day Sufism, primarily within social and economic contexts. The results of the study indicate that Tarekat Al-Idrisiyyah, located in Cisayong, Tasikmalaya Regency, has established 18 business units across various industries, including finance and animal husbandry, with a total economic asset worth approximately IDR 25 billion. In addition, Tarekat Shiddiqiyyah has also established nonprofit business institutions for both its members and the local community, such as Yusro Alfamart, a collaboration between the Shiddiqiyah Order and PT. Sumber Alfalia Trijaya (Sampoerna Group).